Drosophila rab GDI mutants disrupt development but have normal rab membrane extraction. - Ricard, C.S.; Jakubowski, J.M.; Verbsky, J.W.; Barbieri, M.A.; Lewis, W.M.; Fernandez, G.E.; Vogel, M.; Tsou, C.; Prasad, V.; Stahl, P.D.; Waksman, G.; Cheney, C.M. (genesis, 2001)
Rab GTPases are essential for vesicular transport. Rab GDP dissociation inhibitor (GDI) binds to GDP-bound rabs, removes rabs from acceptor membranes and delivers rabs to donor membranes. We isolated lethal GDI mutations in Drosophila and analyzed their developmental phenotypes. To learn how these mutations affect GDI structure, the crystal structure of Drosophila GDI was determined by molecular replacement to a resolution of 3.0 A. Two hypomorphic, missense mutations are located in domain II of GDI at highly conserved positions, but not in previously identified sequence conserved regions. The mutant GDIs were tested for ability to extract rabs from membranes and showed wild-type levels of rab membrane extraction. The two missense alleles showed intragenic complementation, indicating that domain II of GDI may have two separable functions. This study indicates that GDI function is essential for development of a complex, multicellular organism and that puparium formation and pole cell formation are especially dependent on GDI function.